Japan ODA for human resource development support in Vietnam - Nguyễn, Thị Thanh Hoa (Đại học Quốc gia Hà Nội, 2020)
Japan has been a significant aids donor to Vietnam for 30 years. It is proved that human resource development is a problem to address not only for the time being but also for the time to come with regard to a sustainable economic growth. Vietnam has made it dear that it is striving to build a strong and compelitive aconomy. Therefore, the country is seeking for all available instruments to enhance its human resource, the base of its economy. It is no doubt that Japanese ODA has been of great help